2021
DOI: 10.1101/2021.04.03.438283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired top-down auditory processing despite extensive single-neuron responses during human sleep

Abstract: Sleep is defined as a reversible, homeostatically-regulated state of a reduced behavioral responsiveness, and a high arousal threshold in response to external sensory stimulation defines sleep across all species. However, it remains unclear whether sleep mainly gates motor output or affects responses along sensory pathways, and if sleep primarily modulates specific aspects of the sensory response such as feedforward vs. feedback signaling. Here, we simultaneously recorded polysomnography, iEEG, microwire LFPs,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…During deep anesthesia, responses to high-frequency stimuli are attenuated in cat visual cortex (Rager, 1998) and in rodent somatosensory (Castro-Alamancos, 2004) and auditory cortex (Marguet and Harris, 2011). In natural sleep and light propofol anesthesia, auditory cortex of both rodents and humans reveals reduced responses to 40Hz click-trains (Bergman et al, 2022;Hayat et al, 2021;Krom et al, 2020), as has been originally observed with scalp EEG (Lustenberger et al, 2017;Plourde, 1990). Here, we extend these results to show that already during wakefulness, SD-induced Tired conditions entail sensory adaptation at significantly lower frequencies, acting like a low-pass filter that quenches high-frequency neural inputs and diminishes rapid transmission of information across brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During deep anesthesia, responses to high-frequency stimuli are attenuated in cat visual cortex (Rager, 1998) and in rodent somatosensory (Castro-Alamancos, 2004) and auditory cortex (Marguet and Harris, 2011). In natural sleep and light propofol anesthesia, auditory cortex of both rodents and humans reveals reduced responses to 40Hz click-trains (Bergman et al, 2022;Hayat et al, 2021;Krom et al, 2020), as has been originally observed with scalp EEG (Lustenberger et al, 2017;Plourde, 1990). Here, we extend these results to show that already during wakefulness, SD-induced Tired conditions entail sensory adaptation at significantly lower frequencies, acting like a low-pass filter that quenches high-frequency neural inputs and diminishes rapid transmission of information across brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…How do the present results stand with respect to whether primary cortices are robustly modulated, or largely invariant, to brain states and arousal? On one hand, the effects of states such as sleep and anesthesia are typically more modest in primary cortex than in high-order regions (Davis et al, 2007; Hayat et al, 2021; Krom et al, 2020; Liu et al, 2012; Makov et al, 2017; Nourski et al, 2018, 2016; Sela et al, 2020; Sellers et al, 2015; Sharon and Nir, 2018). Similarly, the effects of neuromodulation, attention, and consciousness are more prevalent in high-order regions compared to early sensory cortex (Atiani et al, 2014; Gelbard-Sagiv et al, 2018; Leopold and Logothetis, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…How do the present results stand with respect to whether primary cortices are robustly modulated, or largely invariant, to brain states and arousal? On one hand, the effects of states such as sleep and anesthesia are typically more modest in primary cortex than in high-order regions (Davis et al, 2007;Hayat et al, 2021;Krom et al, 2020;Liu et al, 2012;Makov et al, 2017;Nourski et al, 2018Nourski et al, , 2016Sela et al, 2020;Sellers et al, 2015;Sharon and Nir, 2018). Similarly, the effects of neuromodulation, attention, and consciousness are more prevalent in high-order regions compared to early sensory cortex (Atiani et al, 2014;Gelbard-Sagiv et al, 2018;Leopold and Logothetis, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…During deep anesthesia, responses to high-frequency stimuli are attenuated in cat visual cortex (Rager, 1998) and in rodent somatosensory (Castro-Alamancos, 2004) and auditory cortex (Marguet and Harris, 2011). In natural sleep and light propofol anesthesia, auditory cortex of both rodents and humans reveals reduced responses to 40Hz click-trains (Bergman et al, 2022;Hayat et al, 2021;Krom et al, 2020), as has been originally observed with scalp EEG (Lustenberger et al, 2017;Plourde, 1990). Here, we extend these results to show that already during wakefulness, SD-induced Tired conditions entail sensory adaptation at significantly lower frequencies, acting like a low-pass filter that quenches high-frequency neural inputs and diminishes rapid transmission of information across brain regions.…”
Section: Discussionmentioning
confidence: 99%